2010
DOI: 10.1111/j.1399-3054.2010.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of organic acids and sugar content in tomato fruits by an abscisic acid‐regulated transcription factor

Abstract: Casaretto, JA (reprint author), Univ Talca, Inst Biol Vegetal & Biotecnol, Talca, Chile.Growing evidence suggests that the phytohormone abscisic acid (ABA) plays a role in fruit development. ABA signaling components of developmental programs and responses to stress conditions include the group of basic leucine zipper transcriptional activators known as ABA-response element binding factors (AREBs/ABFs). AREB transcription factors mediate ABA-regulated gene expression involved in desiccation tolerance and are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 50 publications
4
55
2
Order By: Relevance
“…In this context, AREB/ABF bZIP transcription factors that act as regulators of ABA and stress responses in plants are good candidates for the regulation of ABA-mediated fruit ripening. Moreover, a possible role of AREB/ABF transcription factors has been reported for the ripening climacteric fruits (Bastías et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, AREB/ABF bZIP transcription factors that act as regulators of ABA and stress responses in plants are good candidates for the regulation of ABA-mediated fruit ripening. Moreover, a possible role of AREB/ABF transcription factors has been reported for the ripening climacteric fruits (Bastías et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic tree represents VvABF2 (black circle) and its orthologs (boldface) from the A subgroup of bZIP transcription factors in Arabidopsis (AT) and grape (VIT). The closest ortholog of VvABF2 from tomato (SlAREB1; Bastías et al, 2011) and representative Arabidopsis bZIP transcription factors from other bZIP subgroups (subgroup G, AtGBF2; H, AtHY5; I, AtbZIP29; E, AtbZIP34; D, AtTGA3; S, AtATB2; B, bZIP28; and C, AtBZO2H2) are also reported according to Jakoby et al (2002) and Corrêa et al (2008). The gene identifiers as well as synonyms (published names) are given.…”
Section: Vvabf2 Encodes a Functional Transcription Factormentioning
confidence: 99%
“…In plants, ABA serves to induce senescence while auxins, giberellins and cytokinins can delay senescence in a concentration-dependent manner. 28,[44][45][46] IAA is a plant growth promoting hormone synthesized by many plant growth promoting bacteria including Gluconacetobacter diazotrophicus. 35,47 In contrast to G. diazotrophicus, G. xylinus does not synthesize IAA; however, exogenously supplied, this hormone greatly influenced growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Work performed in citrus fruit further revealed a crosstalk between ABA and ethylene for triggering fruit abscission (Gómez-Cadenas et al, 2000;Agustí et al, 2008). Results obtained in mature sweet cherry, which are very prone to abscission, suggested, however, that the ABA increase observed at late stages of fruit ripening was more likely related to Introduction ethylene in the development and ripening of climacteric fruits, such as nectarine and tomato, is well known (Ziliotto et al, 2008;Zhang et al, 2009b) since several reports suggested that the ABA accumulation just before the peak of ethylene production triggers ethylene biosynthesis responsible for climacteric fruit ripening (Zhang et al, 2001;Zhang et al, 2009a;Bastías et al, 2011). The role of ABA in non-climacteric fruit is less clear in spite of several reports have correlated the increase in ABA levels during fruit ripening with the increase in sugars content and the decrease in organic acids or fruit colouration, which are classical traits occurring during fruit maturation (Giribaldi et al, 2010;Chai et al, 2011;Ren et al, 2011;Gambetta et al, 2011;Li et al, 2012b).…”
Section: Role Of Aba In Plant Growth and Developmentmentioning
confidence: 99%
“…This hormone is also crucial for the regulation of a number of physiological processes under non-stressful conditions (Finkelstein et al, 2002;Gómez-Cadenas et al, 2002;Shinozaki and Yamaguchi-Shinozaki, 2007;Kim et al, 2012). The involvement of ABA in the ripening of both climacteric and non-climacteric fruits has been also studied (Lafuente et al, 1997;Alférez and Zacarías, 1999;Zhang et al, 2001;Rodrigo et al, 2003;Zhang et al, 2009a;Sun et al, 2010;Bastías et al, 2011;Jia et al, 2011). In climacteric fruits, ABA accumulates just before the peak of ethylene production, triggering ethylene biosynthesis responsible for fruit ripening (Zhang et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%